2019
DOI: 10.3390/pathogens8040267
|View full text |Cite
|
Sign up to set email alerts
|

β-HPV 8E6 Attenuates ATM and ATR Signaling in Response to UV Damage

Abstract: Given the high prevalence of cutaneous genus beta human papillomavirus (β-HPV) infections, it is important to understand how they manipulate their host cells. This is particularly true for cellular responses to UV damage, since our skin is continually exposed to UV. The E6 protein from β-genus HPV (β-HPV E6) decreases the abundance of two essential UV-repair kinases (ATM and ATR). Although β-HPV E6 reduces their availability, the impact on downstream signaling events is unclear. We demonstrate that β-HPV E6 de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Recently, β-HPV E6 was also found to impair phosphorylation of Chk1. While this resulted in HR impairment, the mechanism that impaired ATR's ability to phosphorylate Chk1 remains unclear [40]. In the case of EBV, we have shown that active STAT3 transcriptionally upregulates the anti-apoptotic form of caspase 9 which then activates caspase 7 resulting in degradation of claspin, a key adaptor protein [9][10][11].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Recently, β-HPV E6 was also found to impair phosphorylation of Chk1. While this resulted in HR impairment, the mechanism that impaired ATR's ability to phosphorylate Chk1 remains unclear [40]. In the case of EBV, we have shown that active STAT3 transcriptionally upregulates the anti-apoptotic form of caspase 9 which then activates caspase 7 resulting in degradation of claspin, a key adaptor protein [9][10][11].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Among β-HPV proteins, the E6 or β-HPV E6 is best characterized. This report focuses on the E6 from β-HPV 8 (β-HPV 8E6), and its ability to disrupt DNA repair [ 16 , 17 , 18 , 19 ]. Interestingly, β-HPV 8E6 exerts its influence in part by binding and destabilizing the cellular histone acetyltransferase, p300 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models show that certain ␤-HPV E6 genes can contribute to UV-associated carcinogenesis (18,19,23). In vitro studies from our group and others have added molecular details by describing ␤-HPV E6's ability to impair the DDR by destabilizing p300 (18,22,27,28,35,36). Despite this focus on repair, there are DDR-independent pathways that protect genome fidelity (37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%